Can inequalities in political participation explain health inequalities? - Reeves, A; Mackenbach, JP (Elsevier, 2019)
Inequalities in health are pervasive and durable, but they are not uniform. To date, however, the drivers of these between-country patters in health inequalities remain largely unknown. In this analysis, we draw on data from 17 European countries to explore whether inequalities in political participation, that is, inequalities in voting by educational attainment, are correlated with health inequalities. Over and above a range of relevant confounders, such as GDP, income inequality, health spending, social protection spending, poverty rates, and smoking, greater inequalities in political participation remain correlated with higher health inequalities. If ‘politicians and officials are under no compulsion to pay much heed to classes and groups of citizens that do not vote’ then political inequalities could indirectly affect health through its impact on policy choices that determine who has access to the resources necessary for a healthy life. Inequalities in political participation, then, may well be one of the ‘causes of the causes’ of ill-health.